Battery Backup Power System for Electrical Appliances with Two Options of Primary Power Sources - Sabry A.H.; Wan Hasan W.Z.; Alkubaisi Y.; Ab-Kadir M.Z.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Battery management systems; Charging (batteries); Domestic appliances; Electric power supplies to apparatus; Electric power system protection; Electric power systems; Energy storage; Power control; Secondary batteries; Topology; Uninterruptible power systems; Backup power supplies; Balancing circuits; Battery Management; Control methods; Electrical appliances; Operating lifetime; Primary power sources; Short-circuit protection; Electric power system control